18
$\begingroup$

I need to calculate the following indefinite integral:

$$I=\int \frac{1}{\cos^3(x)}dx$$

I know what the result is (from Mathematica):

$$I=\tanh^{-1}(\tan(x/2))+(1/2)\sec(x)\tan(x)$$

but I don't know how to integrate it myself. I have been trying some substitutions to no avail.

Equivalently, I need to know how to compute:

$$I=\int \sqrt{1+z^2}dz$$

which follows after making the change of variables $z=\tan x$.

$\endgroup$
27
$\begingroup$

We have an odd power of cosine. So there is a mechanical procedure for doing the integration. Multiply top and bottom by $\cos x$. The bottom is now $\cos^4 x$, which is $(1-\sin^2 x)^2$. So we want to find $$\int \frac{\cos x\,dx}{(1-\sin^2 x)^2}.$$ After the natural substitution $t=\sin x$, we arrive at $$\int \frac{dt}{(1-t^2)^2}.$$ So we want the integral of a rational function. Use the partial fractions machinery to find numbers $A$, $B$, $C$, $D$ such that $$\frac{1}{(1-t^2)^2}=\frac{A}{1-t}+\frac{B}{(1-t)^2}+ \frac{C}{1+t}+\frac{D}{(1+t)^2}$$ and integrate.

$\endgroup$
10
$\begingroup$

With regards to your questions read this wikipedia page.

$\endgroup$
  • 7
    $\begingroup$ cool.. a wikipedia page just for one integral $\endgroup$ – becko Jun 7 '12 at 2:22
  • $\begingroup$ @becko It kinda makes me feel insignificant that a single seemingly simple integral gets more attention than me. XD $\endgroup$ – Simply Beautiful Art Jan 3 '17 at 19:08
10
$\begingroup$

Hint: rewrite the integral as

$$\int \sec ^3 (x) \, dx$$

Recall the identity $\sec^2(x)=\tan^2(x)+1$.

So, substituting, you get

$$\int\sec(x)(\tan^2(x)+1) \, dx=\int\tan(x)\tan(x)\sec(x) \, dx+\int\sec(x) \, dx.$$

The first integral can be solved by $u$-substitution and integration by parts, while the second, is an identity.

$$\int\tan(x) \, d\sec(x) = \tan(x)\sec(x)-\int\sec(x) \, d\tan(x)$$

But $\int\sec(x) \, d\tan(x)$ is the original integral. So write an equation and solve for $\int \sec^3(x)dx$

$\endgroup$
10
$\begingroup$

$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,}% \newcommand{\dd}{{\rm d}}% \newcommand{\down}{\downarrow}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\half}{{1 \over 2}}% \newcommand{\ic}{{\rm i}}% \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\ol}[1]{\overline{#1}}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align} &\color{#c00000}{\int\sec^{3}\pars{x}\,\dd x}= \int\sec\pars{x}\,\dd\tan\pars{x} = \tan\pars{x}\sec\pars{x} - \int\tan\pars{x}\bracks{\sec\pars{x}\tan\pars{x}}\,\dd x \\[3mm]&= \tan\pars{x}\sec\pars{x} - \int\sec^{3}\pars{x}\,\dd x +\int\sec\pars{x}\,\dd x \\[3mm]&= \tan\pars{x}\sec\pars{x} - \color{#c00000}{\int\sec^{3}\pars{x}\,\dd x} + \ln\pars{\sec\pars{x} + \tan\pars{x}} \end{align}

$$\color{#0000ff}{\large% \int\sec^{3}\pars{x}\,\dd x = \half\bracks{\tan\pars{x}\sec\pars{x} + \ln\pars{\vphantom{\LARGE A}\sec\pars{x} + \tan\pars{x}}}} $$

$\endgroup$
4
$\begingroup$

Immediate calculation of $$\int \sec ^{3}xdx.$$

We need the basic formulas of the first two derivatives of $\sec x:$\begin{eqnarray*} (\sec x)^{\prime } &=&\sec x\tan x \\ (\sec x)^{\prime \prime } &=&2\sec ^{3}x-\sec x \end{eqnarray*} Then \begin{eqnarray*} \int \sec ^{3}xdx &=&\frac{1}{2}\int \sec xdx+\frac{1}{2}\int (\sec x)^{\prime \prime }dx \\ &=&\frac{1}{2}\ln \left\vert \sec x+\tan x\right\vert +\frac{1}{2}(\sec x)^{\prime }+C \\ &=&\frac{1}{2}\ln \left\vert \sec x+\tan x\right\vert +\frac{1}{2}\sec x\tan x+C. \end{eqnarray*}

$\endgroup$
2
$\begingroup$

It appears that Mathematica is using the "universal change" for trigonometric integrals $\tan(x/2)=t$: http://en.wikibooks.org/wiki/Calculus/Integration_techniques/Tangent_Half_Angle.

$\endgroup$
2
$\begingroup$

$\int \sqrt (1 + x^2) dx$

let $x = \tan \theta $

then $dx = \sec ^2\theta d\theta $

we have the integral is then: $\int \sec ^3\theta d\theta $

recall: $\tan ^2\theta + 1 = \sec ^2\theta $ and write as: $\int \sec \theta (\sec ^2\theta )d\theta $

continue with integration by parts, by letting:

$u = \sec \theta $

and

$dv = \sec ^2\theta d\theta $

we have:

$v = \tan \theta $

and

$du = \sec \theta \tan \theta d\theta $

and thus,

$uv - \int vdu$

is then:

$\sec \theta \tan \theta - \int \sec \theta \tan ^2\theta d\theta $

recall:

$\tan ^2\theta + 1 = \sec ^2\theta $

we have:

$\sec \theta \tan \theta - \int \sec \theta (\sec ^2\theta - 1) d\theta $

after distribution, altogether we have:

$\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \int \sec ^3\theta d\theta - \int \sec \theta d\theta $

rearranging and collecting like-terms:

$2\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \int \sec \theta d\theta $

$2\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |$

$\int \sec ^3\theta d\theta = (1/2)[\sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |]$

+++++++++++++++++++++++++++

without u\sin g integration tables, we can derive

$\int \sec \theta d\theta $

..........

$=\int 1/\cos \theta d\theta $

$=\int \cos \theta /\cos ^2\theta d\theta $

$=\int \cos \theta /(1 - \sin ^2\theta ) d\theta $

let $u = \sin \theta $

then $du = \cos \theta d\theta $

we have: $\int 1/(1 - u^2) du$

partial fractions:

$A/(1 - u) + B/(1 + u) = 1$

$A + B = 1$

$A - B = 0$

$A = 1/2$

$B = 1/2$

we have:

$-(1/2)\ln |1 - u| + (1/2)\ln |1 + u|$

by rules of logarithms:

$(1/2)\ln |(1 + u)/(1 - u)|$

$(1/2)\ln |(1 - u^2)/(1 - u)^2|$

by rules of logarithms:

$\ln |\sqrt (1 - u^2)/(1 - u)|$

recall:

$u = \sin \theta $

$\ln |\sqrt (1 - \sin ^2\theta )/(1 - \sin \theta )|$

$\ln |\sqrt \cos ^2\theta /(1 - \sin \theta )|$

$\ln |\cos \theta /(1 - \sin \theta )|$

$\ln |\cos \theta (1 + \sin \theta )/(1 - \sin ^2\theta )|$

$\ln |\cos \theta (1 + \sin \theta )/\cos ^2\theta |$

$\ln |1/\cos \theta + \sin \theta /\cos \theta |$

$\ln |\sec \theta + \tan \theta |$

++++++++++++++++++++++++++++

but the integral of $\int \sec ^3\theta d\theta $ is:

$\int \sec ^3\theta d\theta = (1/2)[\sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |]$ + CONS\tan T

and \sin ce $\tan \theta = x = x/1 =$ opposite/adjacent, with the pythagorean theorem, we derive: hypotenuse = $\sqrt (1 + x^2)$ and thus, $\sec \theta $ = hypotenuse/adjacent = $\sqrt (1 + x^2)$

$\int \sqrt (1 + x^2) dx$ $= (1/2)[x\sqrt (1 + x^2) - \ln |\sqrt (1 + x^2) + x|]$ + CONS\tan T

$\endgroup$
1
$\begingroup$

Let $I = \int \sec^3 x dx$

$$\begin{align} I &= \int \sec^3 \;\; \text{(by parts)} \\ &= \int \sec^2 x \sec x dx \\ &= \tan x \sec x - \int \tan x (\sec \tan x) dx \\ &= \tan x \sec x - \int \sec x (\sec^2 x - 1) dx\\ &= \tan x \sec x - I \int \sec x dx \;\; \text{( No need for "c" yet; still an integral to go)} \end{align}$$

Rearrange:

$$2I = \sec x \tan x + \int \sec x dx$$ so

$$ I - (1/2) \sec x \tan x + \ln (A (\sec x + tan x)) $$ (here, $c = ln|A|$)

For int sqrt (1 + z^2) dz put z = sinh u and obtain an equivalent result

$\endgroup$
1
$\begingroup$

For the integral: $$\int \sqrt{1+x^2}dx$$ Put $x=\sinh(u), dx=\cosh(u)du$ The integral becomes: $$\int (\cosh(u))^2 du$$ Use the definition $$\cosh(u)=\frac{e^u+e^{-u}}{2}$$ to see the integral becomes: $$\int \frac{e^{2u}+2+e^{-2u}}{4}du$$ So remembering $$\int e^{au}du=\frac{e^{au}}{a}$$ The integral evaluates to: $$\frac{e^{2u}}{8}+\frac{e^{-2u}}{-8}+\frac{u}{2}+C=\frac{\sinh(2u)}{4} +\frac{u}{2}+ C=\frac{\sinh(u)\cosh(u)}{2} +\frac{u}{2}+ C $$ Putting every thing in terms of x, the integral is $$\frac{x\sqrt{x^2+1}}{2}+\frac{\sinh^{-1}(x)}{2}+C$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.